Aktivitas Antibakteri Fraksi Aquades, Diklorometana dan N-Heksana Daun Majapahit (Crescentia cujete L.) terhadap Bakteri Escherichia coli ATCC 25922 Secara In-Vitro - Huda, Choirul; Martha, Rahma Diyan; Wulandhari, Niken Desi (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
Escherichia coli is a gram - negative bacteria which is able to cause infectious diseases in humans, including urina ry tract infections, stomach cramps, and diarrhea. The purpose of this study was to determine the antibacterial activity of the Majapahit leaf fraction and the optimum concentration to inhibit Escherichia coli bacteria. Majapahit leaves were extracted by t he maceration method using 70% ethanol f ollowed by fractionation using aqua dest solvent, dichloromethane, and n - Hexane. Phytochemical screening of Majapahit leaf extract for the content of flavonoids, alkaloids, and saponins. Antibacterial activity test us ing paper disc diffusion method with positive control of chloramphenicol and negative control of 10% DMSO. The results of phytochemical screening of extracts were positive to flavonoid compounds, alkaloids, and saponins. The results of the antibacterial ac tivity test of the Majapahit leaf fraction had an antibacterial activity which was indicated by the presence of a clear zone around the disc. The aqua dest fraction is the most active fraction that can inhibit Escherichia coli bacteria. Based on the data a nalysis that has been carried out, it can be concluded that the use of different types of solvents did not produce significant differences in inhibiting Escherichia coli bacteria.